Growing information asymmetries as the cloud spreads - Primavera De Filippi (Internet Policy Review, 2013)
To the extent that they provide content or information to the public, many cloud operators can be regarded as infomediaries - information intermediaries between users looking for information and the supplier of that information. As a general rule, 'infomediaries' are considered to be neutral providers of information. People often believe that the information they provide is unbiased, as they do not act on behalf of any third-party supplier or vendor, nor do they try to promote any type of information over the other. However, this situation is seldom true in the context of cloud computing, as many cloud operators have the discretionary power to decide exactly what kind of information is made available to the public and how that information is presented. While there are many ways in which this could affect the experience (and satisfaction) of end-users, this article analyses how hierarchies of information curation and distribution fundamentally challenge the user's right to access to information.
Keywords: 300; Cloud computing; Infomediary; User-generated content; Freedom of expression; Information bias; Censorship